Experimental and simulation analysis of energy absorption capacity of 3D printed structure design (D) - Goh, Jun Yi (Nanyang Technological University, 2023)
Ansys Mechanical is a software that is convenient and easy to use. It is a finite element-based simulation tool that is effective and integrates seamlessly with Ansys’ large variety of Multiphysics solvers. With a variety of methodical tools, individuals can take their geometrical phase through endorsed proof of concept simulations, optimisation, and validation. This software is utilised to determine the best speed to find the optimised internal energy of the model. An experiment is also done by printing the model and testing it for the internal energy using compressive forces and impact loading. This tests the model to ensure that its functional and safe to use for large structures.